Entre barquinhos, carrões e um disco voador: como o sujeito se posiciona nas canções brasileiras dos anos 1960 : ethos e modalização - Paulo, Lucineide Lima de (2010)
This paper aims at analyzing the image and the attitude of the subject of Brazilian songs of the 1960 s. For this purpose, this thesis analyzes a corpus consisting of twenty texts, from the viewpoint of the Semiolinguistic Theory of Discourse Analysis, as proposed by Patrick Charaudeau, with the support of studies on Modalization and Ethos. Yet, interpretative resources which might contribute to a suitable reading of the text by the students, such as strategies of Textual Linguistics, were here included. The objective of this work is to discuss prospective ways for interpreting texts which portray a temporal distance from the reader. Initially, the texts were read based on the theory of Discourse Analysis, which considers the context of production relevant for a coherent reading. Therefore, the historical and cultural factors were made salient. It was likewise evaluated that distinguishing the images constructed by enunciators would contribute to the text comprehension, for this reason the concept of ethos was pondered. These subjects manifested themselves in songs, and were sometimes more and sometimes less engaged, aspect which was verified by means of implicit and explicit Modalization. We analyzed twenty song lyrics of different styles, released in Brazil in the 60 s: samba-canção, bossa nova, jovem guarda, protest music and tropicalismo. Following the analysis of each text, a set of activities was designed to be applied in a High School class. The exercises focus on the notion that the subject who produces the text is historically marked what makes it relevant to consider the context of production. However, the activities allow, as well, both teacher and student to realize that the subject is capable of making choices what may generate a mask, an image of itself, reflecting its position, its attitude in relation to the discourse and the interlocutor. In developing this research, the prevalence of epistemic modalization in the texts was established as evidence that the composer seeks to express knowledge and does so with conviction, in other words, without expressing doubt. The ethé which are generated, unlike the initial hypothesis, do not faithfully represent the style of the composers or of the performers, or even the style of the song. Thus, it is not appropriate to unify the composers, for instance, under a particular label because of the constructed images in the previous songs. Not even a style, such as bossa nova or tropicalismo, illustrates one single representation, and therefore it is not predictable. All these factors must be considered during class whenever it is text interpretatio n takes place.